Evaluasi Pengelolaan Barang Milik Negara (BMN) Berupa Penggunaan Barang Milik Negara (BMN) Pada Biro Layanan Pengadaan dan Pengelolaan Barang Milik Negara Sekretariat Jenderal Kementerian Perhubungan - Tripta Tranggana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out whether the evaluation of BMN management in the form of the use of BMN at the LPPBMN Bureau of the Secretariat General of the Ministry of Transportation has been carried out and how effective the management of BMN is and to find out what obstacles and obstacles there are in managing BMN at the LPPBMN Bureau of the Secretariat General of the Ministry of Transportation. This research applies descriptive qualitative research methods, where data sources are obtained through interviews with agency employees. Research data includes the results of interviews, field observations, documentation, as well as information from previous research which is used as a theoretical reference. The results of this research show that BMN management at the LPPBMN Bureau is running based on statutory regulations, namely referring to Presidential Regulation Number 16 of 2018 concerning Procurement of Government Goods or Services through the RKBMN (State Property Requirements Plan) process which is guided by Minister of Finance Regulation Number 153 of 2021, then in PSP it is based on PMK No. 76 of 2019 concerning the second amendment to PMK no. 246 of 2019 concerning Procedures for Implementing the Use of BMN. All administrative information about BMN is listed in the SIMAN and SAKTI systems by the Ministry of Finance, including information about the condition of the goods themselves.